Educational Interventions to Improve Antibiotic Dispensing by Community Pharmacists - Herdeiro, Maria Teresa (2016)
Objectives To carry out a critical review about educational interventions on community pharmacists, to improve antibiotic dispensing habits and/or behaviours. Methods Review all studies published, from January 2001 to December 2010, about educational interventions in pharmacists to improve antibiotic use in primary care, by searching the scientific MEDLINE database, using PubMed. Data extraction included study design, type of interventions, population targeted, and results of outcomes measured, i.e. changes on total of antibiotic used and/or adherence to guidelines, and, quality of pharmacy practice. Results Our search retrieved seven studies about interventions in pharmacists to improve antibiotic use. In five studies the interventions covered both pharmacists and physicians and were extended to patients and their caregivers or general population. We found only two studies that addressed interventions specifically designed to improve pharmacists’ to combat the dispensing of antibiotics without prescription. Educational interventions included (1) dissemination of printed/audiovisual educational materials (2) group education, including group-session rounds, and (3) individual outreach visits or (4) pamphlets to patients. Results reported by author were positive for all outcomes measured in five studies, positive for some outcomes and negative for others in two studies and negative for all outcomes in one study. Conclusions There are few studies published about educational interventions directed specifically to pharmacists, but results in this study indicated that pharmacists practice could be improved with educational interventions and multidisciplinary interventions could improve antibiotic use. Even that, some author stressed the usefulness of including pharmacists in teams tasked with drawing up recommendations and making decisions about antibiotic use in certain countries. Accordingly this, we think that is important to develop interventions directed to pharmacists for improvement of antibiotic use.